Volumetric and chromatic reintegration in conservation of in situ glazed tiles - Mendes, Marta T. (2016)
Volumetric and chromatic reintegration is one of the most important but challenging treatments in conservation of in situ glazed tiles due to the need to protect them from water intrusion and further deterioration despise the demanding conditions and requirements needed in outdoor exposure. A set of six infill pastes based on aerial lime, hydraulic lime, aerial lime plus vinylic resin, epoxy resin and polyester resin binders was selected based on materials applied in previously reported interventions and the experience of professionals working in the field. The laboratory studies included the characterization of the infill pastes with and without chromatic reintegration/coating layer (SEM, MIP, porosity, water absorption, water vapour permeability, adhesion to the ceramic) and their behaviour after cure, artificial ageing (salt ageing, UV-Temp-RH cycles) and natural ageing. The results obtained allowed to formulate some considerations about these materials, their different characteristics and their performance when applied in the infill of architectural tile lacunae. The laboratory results have been compared with the performance of similar treatments surveyed on sites where they had been applied.